Five‐year results from the prospective European multicentre cohort study on radiofrequency segmental thermal ablation for incompetent great saphenous veins. Issue 3 (February 2015) - Proebstle, T. M.; Alm, B. J.; Göckeritz, O.; Wenzel, C.; Noppeney, T.; Lebard, C.; Sessa, C.; Creton, D.; Pichot, O.
<x xml:space="preserve">Abstract</x> Background This was a prospective study of radiofrequency segmental thermal ablation (RFA) for the treatment of incompetent varicose great saphenous veins (GSVs). The present report describes long‐term follow‐up at 5 years. Methods The 5‐year follow‐up of this multicentre European study included assessment of the Venous Clinical Severity Score (VCSS), and GSV occlusion and reflux on duplex imaging. Results A total of 225 patients had 295 GSVs treated by RFA, achieving an initial vein occlusion rate of 100 per cent. With 80·0 per cent compliance, Kaplan–Meier analyses showed a GSV occlusion rate of 91·9 per cent and a reflux‐free rate of 94·9 per cent at 5 years. Among the 15 GSVs noted with reflux during follow‐up, only three showed full recanalization of the GSV at 1 week, 6 months and 3 years. Of the 12 legs with partial recanalization, reflux originated at the saphenofemoral junction in ten, with a mean length of the patent segment of 5·8 (range 3·2–10) cm; only six patients were symptomatic. Mean(s.d.) VCSS scores improved from 3·9(2·1) at baseline to 0·6(1·2), 0·9(1·3) and 1·3(1·7) at 1, 3 and 5 years. Conclusion At 5 years RFA proved to be an efficient endovenous treatment for incompetent GSVs in terms of sustained clinical and anatomical success for the vast majority of treated patients.